Fostering Curiosity about Social Responsibility and Marketing Ethics - Venkat Yanamandram (Australasian Accounting, Business and Finance Journal, 2009)
Last year, I was strolling through my local veggie shop after visiting the supermarket, and I noticed that the prices of avocados and apples were the same at both the retailers. Later that week, a news item on current affairs confirmed my suspicion that the supermarket was engaged in squeezing smaller grocery operators out of the market by adopting aggressive pricing tactics amongst many other unethical practices including selling some products at weights substantially less than those marked on the package and subsidising fuel discount by charging more at the checkout. Yet, this supermarket was involved in a broad range of community and environmental initiatives. These observations made me wonder if students ever assess the total impact of all marketing decisions.